Actividad leishmanicida del aceite esencial de Plumbago scandens L. en promastigotes de Leishmania major like - Puchaicela Quirola, Jorge David (2018)
Cutaneous and mucocutaneous Leishmaniasis is a disease caused by several species of the genus Leishmania and transmitted by the bite of various hematophagous species of the genus Lutzomia. For its treatment, pentavalent antimonial drugs such as N-methylglucamine (Glucantime) are used, which are the first choice. Alternatively, in traditional medicine empirical medicinal plants are used to treat this disease, without an entire knowledge about its benefits and mechanism of action, being one of them Plumbago scandens L. (Plumbaguinaceae). The present study was designed to evaluate the leishmanicidal activity of the essential oil of Plumbago scandens L. which was extracted from the aerial parts (stems and leaves) by steam distillation and was evaluated its activity on axenic promastigotes of L. major like and the percentage of growth inhibition of the parasites determinated. The determination of the inhibition percentage was based on the metabolic reduction of 3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazole bromide (MTT) by mitochondrial succinate-dehydrogenase to a blue-violet colored compound, with maximum absorbance at 570 nm. The reference drug used was amphotericin B. The results showed that the essential oil inhibits in 85% the development of the parasite at concentrations of 15-30 μg/ml, causing the lysis of these and inhibiting their reproduction and motility, at the same time, amphotericin alone caused the inhibition of its division; the results obtained in the research were socialized to Students and Teachers of the Clinical Laboratory Career of National University of Loja. Keywords: Leishmania major like, leishmanicide, Leishmania, essential oil, Plumbago scandens L, MTT